Kontroll över kontroll : funktioner i ett språkkontrollprogram för svenska med tanke på andraspråksinlärare på universitetsnivå - Pilke, Nina, 1968- (Vaasa : Vaasan yliopisto, 2007)
Abstract: Control over control : functions in a language tool for Swedish with regard to L2 learners at university level.
Keywords: ruotsin kieli; oikeakielisyys; tarkastus; korjausluku; tietokoneohjelmat; Svefix; käyttäjätutkimus